2019
DOI: 10.2147/ijn.s197099
|View full text |Cite
|
Sign up to set email alerts
|

<p>Biological response of chemically treated surface of the ultrafine-grained Ti&ndash;6Al&ndash;7Nb alloy for biomedical applications</p>

Abstract: Background: Nanophase surface properties of titanium alloys must be obtained for a suitable biological performance, particularly to facilitate cell adhesion and bone tissue formation. Obtaining a bulk nanostructured material using severe plastic deformation is an ideal processing route to improve the mechanical performance of titanium alloys. By decreasing the grain size of a metallic material, a superior strength improvement can be obtained, while surface modification of a nanostructured surface can produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 38 publications
1
13
0
3
Order By: Relevance
“…Oliveira et al [16] reported that Ti-6Al-7Nb alloy processed by ECAP with an average grain size~200 nm had higher fatigue properties, which make it suitable for practical application. At the same time, a highly bioactive behavior of UFG Ti-6Al-7Nb alloy after phosphoric acid etching, regardless of the usage of alkaline treatment, was reported by Oliveira et al [17].…”
Section: Introductionmentioning
confidence: 57%
See 1 more Smart Citation
“…Oliveira et al [16] reported that Ti-6Al-7Nb alloy processed by ECAP with an average grain size~200 nm had higher fatigue properties, which make it suitable for practical application. At the same time, a highly bioactive behavior of UFG Ti-6Al-7Nb alloy after phosphoric acid etching, regardless of the usage of alkaline treatment, was reported by Oliveira et al [17].…”
Section: Introductionmentioning
confidence: 57%
“…Recently, ultrafine-grained (UFG) and nanocrystalline (NC) materials processed by severe plastic deformation (SPD) have been widely investigated and found to have unique physical and chemical properties [11][12][13]. Enhanced mechanical behavior and biocompatibility of UFG/NC Ti-6Al-7Nb alloy were acquired after the SPD process [14][15][16][17][18][19]. For instance, Polyakova et al [9] revealed that the tensile strength of the UFG Ti-6Al-7Nb alloy with grain size of 330 nm increased to 1210 MPa after equal channel angular pressing (ECAP), which was 20% higher than observed in coarse-grained (CG) counterparts.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous physical and chemical surface modifications can and have been applied to metallic biomaterials in general [11], specifically to titanium-based materials [12], and most recently to the application of nano-modifications [13]. This has led to the invention of many new types of titanium-based orthopedic materials with not only a higher resistance to corrosion and better tribological properties [14,15], but also improved mechanical properties [16][17][18][19]. In addition, biocompatibility [19] and resistance to bacterial infections [12,[20][21][22] can be positively influenced by those newly developed materials.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no evidence that a very rough surface (Ra > 5 μm) promotes specific effects on osteoblast differentiation, 38 and there is no consensus on a maximum roughness value considered detrimental to cell biology during osseointegration or on the optimal roughness for osteoblast differentiation. 25,30 The rough surface of SLM samples was also observed in SEM images, with the presence of spherical particles that were not fused, partially fused, or weakly attached to each other. These findings can be due to the parameters used in the SLM technique such as material, particle size of the Ti powder, layer thickness, laser type and power, and scanning parameters.…”
Section: Discussionmentioning
confidence: 93%
“…A conventional heating plate was used to heat the acid medium to 80 C and then the samples were immersed in the solution for 30 min. Afterwards, the samples underwent an alkaline treatment by immersion into 75 ml of NaOH solution at 10 mol/L kept at 60 C for 24 h[29][30] (Table 1)(Figure 1).…”
mentioning
confidence: 99%